Sistem Keamanan Ruang Server BHS (Baggage Handling System) Kualanamu Berbasis IoT: Kualanamu IoT-Based BHS (Baggage Handling System) Server Room Security System - A F Limas Ptr; B H Hayadi; G Prayatna (Cered Indonesia Institute, 2022)
Along with the increasing level of criminal data theft that occurs, a room security system is needed that good for maintaining information security of a particular agency or organization. A good security system is a security system that can be monitored and controlled remotely using the web or better known as IoT (Internet of Things). In this research, a language room security system (baggage handling system) will be designed. Kualanamu airport based on IoT using an android application, this system works using several modules including an RFID (Radio Frequency Identification) module, a camera module and an entrance lock solenoid. The RFID card in this RFID module functions as a process of identifying people who want to enter the room. In addition, this RFID module also functions as a trigger for the camera to work to take pictures of people who want to enter the room. The information obtained from both modules will be sent to the Android application. Room administrators can carry out a verification process to allow or deny people who want to enter the room. The test results of this system can run well when the web speed of the access point is fast and stable, but less than ideal when the web speed of the access point is slow.